Imatinib mesylate as add-on therapy for pulmonary arterial hypertension - Höper, Marius; Barst, Robyn J.; Bourge, Robert C.; Feldman, Jeremy; Frost, Adaani E.; Galié, Nazzareno; Gómez-Sánchez, Miguel Angel; Grimminger, Friedrich; Grünig, Ekkehard; Hassoun, Paul M.; Morrell, Nicholas W.; Peacock, Andrew J.; et al. (Circulation, 2013)
Background—By its inhibitory effect on platelet-derived growth factor signaling, imatinib could be efficacious in treating patients with pulmonary arterial hypertension (PAH).Methods and Results—Imatinib in Pulmonary Arterial Hypertension, a Randomized, Efficacy Study (IMPRES), a randomized, double-blind, placebo-controlled 24-week trial, evaluated imatinib in patients with pulmonary vascular resistance ≥800 dyne·s·cm−5 symptomatic on ≥2 PAH therapies. The primary outcome was change in 6-minute walk distance. Secondary outcomes included changes in hemodynamics, functional class, serum levels of N-terminal brain natriuretic peptide, and time to clinical worsening. After completion of the core study, patients could enter an open-label long-term extension study. Of 202 patients enrolled, 41% patients received 3 PAH therapies, with the remainder on 2 therapies. After 24 weeks, the mean placebo-corrected treatment effect on 6-minute walk distance was 32 m (95% confidence interval, 12-52; P=0.002), an effect maintained in the extension study in patients remaining on imatinib. Pulmonary vascular resistance decreased by 379 dyne·s·cm−5 (95% confidence interval, −502 to − 255; P<0.001, between-group difference). Functional class, time to clinical worsening, and mortality did not differ between treatments. Serious adverse events and discontinuations were more frequent with imatinib than placebo (44% versus 30% and 33% versus 18%, respectively). Subdural hematoma occurred in 8 patients (2 in the core study, 6 in the extension) receiving imatinib and anticoagulation.Conclusions—Imatinib improved exercise capacity and hemodynamics in patients with advanced PAH, but serious adverse events and study drug discontinuations were common. Further studies are needed to investigate the long-term safety and efficacy of imatinib in patients with PAH.Clinical Trial Registration—URL: http://www.clinicaltrials.gov. Unique identifier: NCT00902174 (core study); NCT01392495 (extension).
Gesehen am 29.06.2021